HUBUNGAN PENGETAHUAN DAN SIKAP BIDAN DENGAN PELAKSANAAN PROGRAM 10 T DALAM PELAYANAN ANTENATAL CARE (ANC) DI PUSKESMAS HAMPARAN PERAK - Meiyana Sinaga (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2019)
According to WHO data (2015), it is estimated that around 15% of all pregnant women will develop complications related to pregnancy. The purpose of this research is to know the Relationship between Knowledge and Attitudes of Midwife with the Implementation of the 10 T Program of Antenatal Care (ANC) in the Puskesmas Hamparan Perak in 2019. This research was conducted with an analytical survey research design with cross sectional approach. The population in this study amounted to 43 respondents. The sampling technique uses total pollulation. Data analysis usesunivariate, bivariate analysis. The results of the study can be known that there is knowledge of midwives with the implementation of the 10 T program in Antenatal Care (ANC) chi-square test results sig p-value 0.026 <a (0.05). There is a relationship between midwives' attitudes and the implementation of the 10 T program in Antenatal Care (ANC) chi-square test results sig p-value 0.032 <a (0.05). Chi-square test results sig p-value 0.038 <(0, 05), in the Puskesmas Hamparan Perak in 2019. Based on the results of the study it can be concluded that there is a relationship between knowledge and attitude of midwives with the implementation of the 10 T program in Antenatal Care (ANC) service in the Puskesmas Hamparan Perak in 2019. It is hoped that health workers will further improve the quality of services in the implementation of 10 T so that services with standards procedur.